(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
This scientific article provides a detailed analysis of the legal framework for the organization of law enforcement agencies, in particular, the legislative system. The article also highlights a number of key trends in reforms in this area through the analysis of regulatory documents.